2006
DOI: 10.1158/1078-0432.ccr-05-1576
|View full text |Cite
|
Sign up to set email alerts
|

Effective cancer therapy with the alpha-particle emitter [211At]astatine in a mouse model of genetically modified sodium/iodide symporter-expressing tumors.

Abstract: Purpose: The sodium/iodide symporter (NIS) gene is currently explored in several trials to eradicate experimental cancer with radiodine ( 131 I) by its h-emission. We recently characterized NIS-specific cellular uptake of an alternative halide, radioastatine ( 211 At), which emits high-energy a-particles.The aim of this study was to investigate in vivo effects of the high linear energy transfer (LET) emitter 211 At on tumor growth and outcome in nude mice. Experimental Design: We administered radioastatide in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…The well known additional antiproliferative and radiosensitizing effects of retinoids in breast cancer cells [42][43][44][45] as well as the bystander effect caused by the crossfire effect of b-particles emitted by 131 I are able to potentiate the therapeutic effect of 131 I in vivo [46,47]. Should limited iodide accumulating capacity and short iodide retention limit therapeutic efficacy of 131 I in breast cancer, the application of alternative radionuclides, including the high energy a-emitter 211 Astatine ( 211 At) and the potent b-emitter 188 Rhenium ( 188 Re), that are also transported by NIS, can be considered for application following atRA/Dex-mediated induction of endogenous NIS expression in breast cancer due to their higher energy and shorter half-life, thereby offering the possibility of higher energy deposition in a shorter time period [48][49][50][51][52][53]. Stimulation of the tumor absorbed radiation dose and the therapeutic effect of NIS-mediated radionuclide therapy has already been demonstrated for 188 Re in NIS-expressing mammary adenocarcinomas in a transgenic mouse model [48,49,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…The well known additional antiproliferative and radiosensitizing effects of retinoids in breast cancer cells [42][43][44][45] as well as the bystander effect caused by the crossfire effect of b-particles emitted by 131 I are able to potentiate the therapeutic effect of 131 I in vivo [46,47]. Should limited iodide accumulating capacity and short iodide retention limit therapeutic efficacy of 131 I in breast cancer, the application of alternative radionuclides, including the high energy a-emitter 211 Astatine ( 211 At) and the potent b-emitter 188 Rhenium ( 188 Re), that are also transported by NIS, can be considered for application following atRA/Dex-mediated induction of endogenous NIS expression in breast cancer due to their higher energy and shorter half-life, thereby offering the possibility of higher energy deposition in a shorter time period [48][49][50][51][52][53]. Stimulation of the tumor absorbed radiation dose and the therapeutic effect of NIS-mediated radionuclide therapy has already been demonstrated for 188 Re in NIS-expressing mammary adenocarcinomas in a transgenic mouse model [48,49,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic potential of a-emitters for macroscopic tumors has been sparsely investigated, and the dose levels required for tumor eradication are mostly unknown. A few studies have reported complete remission at absorbed doses of 12-21 Gy (14,29,30). Other studies reported antitumor effects that were close to, but not, curative (TFF, 60%-95%) for doses of 9-28 Gy (31-37).…”
Section: Discussionmentioning
confidence: 99%
“…Measles virus expressing NIS is already in the clinic and would seem to be an ideal initial model. The assessment of alternative radioisotopes, such as 186 Re, 188 Re, or 211 At, [18][19][20] would offer the prospect of integrating this approach within a standard outpatient regimen of radiation delivery.…”
Section: Discussionmentioning
confidence: 99%